2005
DOI: 10.1080/13546800444000047
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and switching on verbal and figural fluency functions in adults with attention deficit hyperactivity disorder

Abstract: The results of the present study suggest that adult patients with ADHD may suffer from a dysfunction that may affect retrieval processes and the categorisation of knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
49
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 77 publications
(122 reference statements)
5
49
1
5
Order By: Relevance
“…Classical scoring of the verbal fluency tasks records the number of correctly generated words and the number of errors which informs us about divergent thinking and executive or language dysfunctions (Lezak, 1995). Most of the studies report phonemic fluency differences in ADHD (Grodzinsky & Diamond, 1992;Loge, Staton, & Beatty, 1990;Sergeant, et al, 2002), but opposite results can be found as well (Fischer, Barkley, Edelbrock, & Smallish, 1990;McGee, Williams, Moffitt, & Anderson, 1989;Reader, Harris, Schuerholz, & Denckla, 1994;Tucha, et al, 2005), where differences were found solely in semantic fluency. These previous findings usually do not explain the reason behind differences of verbal fluency achievement, but it is supposed that phonemic fluency depends on EF more than semantic fluency.…”
Section: Measuring Executive Functions With Verbal Fluency Tasksmentioning
confidence: 84%
See 3 more Smart Citations
“…Classical scoring of the verbal fluency tasks records the number of correctly generated words and the number of errors which informs us about divergent thinking and executive or language dysfunctions (Lezak, 1995). Most of the studies report phonemic fluency differences in ADHD (Grodzinsky & Diamond, 1992;Loge, Staton, & Beatty, 1990;Sergeant, et al, 2002), but opposite results can be found as well (Fischer, Barkley, Edelbrock, & Smallish, 1990;McGee, Williams, Moffitt, & Anderson, 1989;Reader, Harris, Schuerholz, & Denckla, 1994;Tucha, et al, 2005), where differences were found solely in semantic fluency. These previous findings usually do not explain the reason behind differences of verbal fluency achievement, but it is supposed that phonemic fluency depends on EF more than semantic fluency.…”
Section: Measuring Executive Functions With Verbal Fluency Tasksmentioning
confidence: 84%
“…If the fluency scoring protocol measures the number and types of clusters, i.e., a group of similar words, and the switching between those in the oral performance, then it could result in more sensitive indices of language and executive computation (Tucha, et al, 2005). This different approach of verbal fluency focuses on the better specified individual cognitive profiles due to including additional tasks relying on separate skills of strategy using.…”
Section: Measuring Executive Functions With Verbal Fluency Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…A clinical evaluation of symptoms and impairments of patients with ADHD benefits from an objective assessment of neuropsychological functions using standardized psychometric tests. Most theories on neuropsychological functions of adults with ADHD proposed a primary deficit of inhibitory executive functions (Barkley, 1997;Castellanos, Sonuga-Barke, Milham, & Tannock, 2006;Tannock, 1998) which resulted in a large body of research examining various functions associated with executive control, including focused attention, divided attention, vigilance, working memory, inhibition, set-shifting, verbal fluency, and problem solving (Boonstra, Kooij, Oosterlaan, Sergeant, & Buitelaar, 2010;Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005;Dinn, Robbins, & Harris, 2011;Fuermaier et al, 2015;Hervey, Epstein, & Curry, 2004;Lange et al, 2014;Schoechlin & Engel, 2005;O. Tucha et al, 2005, L. Tucha et al, 2008, 2009.…”
mentioning
confidence: 99%